(untitled) (Research, Society and Development, 2024)
The dramatic growth of online learning due to the COVID-19 pandemic has made educational opportunities more accessible to students, who can now access instructional content without traditional time and location restrictions. In this sense, the objective of this study is to analyze whether teaching mathematics to blind students during the COVID-19 pandemic period in a State School provided profitability to teaching. Methodologically, this is qualitative and field research, the results of which are largely positive, with the majority of teachers not supporting inclusion, nor seeing its direct benefits for children with visual impairments due to the lack of physical and human infrastructure to assist them. blind students who need special attention. The data obtained in this study highlighted several relevant aspects of inclusion. It was evident that the regular school teacher needs a learning support assistant, with positive attitudes towards inclusion and who aspires to achieve this for their student.